Control of active front-end rectifier of the solid-state transformer with improved dynamic performance during precharging - Dehghani Tafti, Hossein (2018)
The control of the active front-end rectifier of the three-stage solid-state transformer (SST) system is addressed in this paper. A comprehensive precharging sequence is introduced for the active front-end rectifier of the SST to limit the inrush current during the start-up process to its nominal current. The proposed precharging algorithm consists of two phases, passive and active precharging. The precharging resistor limits the current during the passive precharging, while a ramp increase of the voltage reference is used in the controller during the active precharging to prevent large inrush currents. Additionally, a feed-forward voltage compensator is added to the voltage reference of the controller to improve the dynamic response at the beginning of the active precharging. The proposed algorithm is detailed and simulation results on a 4-kW active front-end converter are presented to validate its performance. The simulation results under various operation conditions show the ability of the proposed algorithm to limit the converter current to its nominal value during the precharging as well as to control the dc-link voltage under different load changes.